Description of the larva of mnesarete pudica (Hagen in Selys, 1853) (Odonata: Calopterygidae) and notes on known genera of south american calopterygidae larvae - Guillermo-Ferreira, Rhainer [UNESP]; Bispo, Pitágoras C. [UNESP] (My University, 2012)
The final instar larva of Mnesarete pudica is described and illustrated based on reared specimens collected in Brazil. This species can be distinguished from others by presenting: a) five palpal and three premental setae; b) no posterodorsal hooks on abdominal segments; c) lateral spines only in S9-10. M. pudica is compared to other South American calopterygids and biological notes are presented. Copyright © 2012 Magnolia Press .
Keywords: Brazil; Damselfly; Dragonfly; Naiad; Neotropical; Nymph; Taxonomy